Retrolaminar Block Versus Paravertebral Block for Pain Relief After Less-Invasive Lung Surgery: A Randomized, Non-Inferiority Controlled Trial - Sugiyama, Takuji; Kataoka, Yuki; Shindo, Kazuo; Hino, Miki; Itoi, Kazumi; Sato, Yukihito; Tanaka, Shiro (Cureus, 2021)
Introduction A retrolaminar block (RLB) is a modified paravertebral technique with a local anesthetic injected at the retrolaminar site. The aim of this non-inferiority, parallel-group, prospective, and randomized study was to compare the analgesic efficacy of the paravertebral block (PVB) and RLB after lung surgery. Methods Eligible subjects were patients aged more than 20 years, with American Society of Anesthesiologists physical status Ⅰ or II, who were scheduled to undergo video-assisted thoracoscopic surgery (VATS) or limited thoracotomy because of lung disease. Patients were randomly allocated to receive either a PVB or RLB using a computer-generated sequence and sealed opaque envelopes. The PVB and RLB were induced by injecting 20 mL of 0.50% ropivacaine and 40 mL 0.25% ropivacaine, respectively. As the primary outcome variable, we considered the area under the curve (AUC) of the postoperative pain intensity using the trapezoidal method. Pain intensity was assessed using an 11-point numerical rating scale (NRS). We converted the NRS (0-10) into the visual analog scale (VAS) (0-100 mm) proportionally. We compared the AUC of the converted NRS (AUC-cNRS) on coughing between one and two hours after the operation. The non-inferiority margin was set at 25 mm × h in the AUC-cNRS. Patients and nurses were blinded to group assignments. Secondary outcomes included time to perform the block, NRS for pain intensity at rest and on coughing at one, two, four, 24, and 48 hours after the operation, the incidence of postoperative nausea and vomiting, time to first morphine use after the operation, and cumulative morphine consumption at 24 and 48 hours after the operation. Results In each group, 25 patients were randomized and analyzed. No significant difference in the AUC-cNRS was noted between the groups (P = 0.117). The mean difference in the AUC-cNRS (group RLB minus group PVB) was 13.42 mm × h, 95% confidence interval, -3.48 to 30.32 mm × h. However, when patients with unexpectedly extended skin incision were excluded from the analysis, the AUC-cNRS of group RLB was significantly higher as compared to group PVB (P = 0.0388). The time to perform the block was longer in PVB as compared to the RLB group (P < 0.0001). No significant differences were noted in the remaining secondary outcomes. Conclusion The non-inferiority of RLB as compared to PVB was not confirmed. Though RLB has the advantage of a shorter time to perform, RLB is not recommended for patients undergoing VATS or limited thoracotomy because of lack of efficacy as compared to PVB.